Xenotransplantation of Cryopreserved Calf Testicular Tissues - Yansen Zhao; Wenqian Zhu; Rui Yang; Boyang Zhang; Bo Tang; Xueming Zhang (Veterinary Sciences)
The cryopreservation of testicular tissues meets the demands for the germplasm preservation of humans and animals. Previously, we reported on the cryopreservation of bovine testicular tissues. To further evaluate the viability of these tissues, subcutaneous xenotransplantation of the frozen–thawed calf testicular tissues was performed with castrated nude mice as the recipients. After 28 days (D28), the survival and development of the grafts were examined. The grafts from 1-day-old (D1) calf testes were recovered and angiogenesis around the grafts was observed. Histologically, the seminiferous cords in the grafts were well maintained and capillaries in the interstitium were observed. Quantitative real-time PCR (qRT-PCR) analysis showed that the grafts expressed germline genes Gfrα-1, C-kit, and Sycp3 and somatic genes Sox9, Acta2, and Star. The expressions of C-kit, Sox9, Acta2, and Star were higher in 28D grafts than those in 1D and 30-day-old (30D) calf testicular controls. Together, we initially demonstrate that cryopreserved calf testicular tissues retain their viability and developmental capacity after xenotransplantation.